새누리 벼 품종 배경 lipoxygenase-3 결핍 자포니카 근동질계통 개발 - 박현수(Hyun-Su Park); 이건미(Keon-Mi Lee); 김기영(Ki-Young Kim); 김정주(Jeong-Ju Kim); 신운철(Woon-Cheol Shin); 백만기(Man-Kee Baek); 김춘송(Choon-Song Kim); 박슬기(Seul-Gi Park); 이창민(Chang-Min Lee); 서정필(Jung-Pil Suh); 조영찬(Young-Chan Cho) (Korean journal of breeding, 2019)
It is reported that the absence of lipoxygenase-3 (LOX-3) may contribute to a reduction in stale flavor after the storage of rice. To improve the quality of stored rice of the Korean japonica rice cultivar, we conducted a breeding program to develop near-isogenic rice without LOX-3 in the genetic background of Saenuri, a mega variety of Korea. In the first step of the breeding program, we used a donor parent of LOX-3 null, Daw Dam, and a recurrent japonica parent, Sindongjin, to develop HR27873-AC12 by backcross (BC1), color test for introgression of lox-3, and anther culture for rapid fixation. In the second step, we used the donor parent, HR27873-AC12, and the recurrent parent, Saenuri, to develop HR28896-31-3-1-1 by backcross (BC1), marker-assisted selection (MAS) for lox-3, and phenotypic selection (PS) for agronomic traits. Finally, in the third step, we developed HR30960-186-2-1-2-1 (Jeonju624), derived from a cross between Saenuri and HR28896-31-3-1-1, by MAS for lox-3 and PS with high selection pressure for agronomic characteristics. Jeonju624 was confirmed with the introgression of lox-3 by molecular marker. Jeonju624 was a mid-late maturing rice with similar agronomic characteristics to Saenuri, lodging tolerance with short culm, erect plant architecture, and resistance to bacterial blight and rice stripe virus. The yield components of Jeonju624 were mostly similar to Saenuri, except for the 1,000-grain weight of brown rice. The appearance of the grain of Jeonju624 was better than that of Saenuri, and the characteristics of cooked rice were similar to those of Saenuri. In the genetic background analysis using 406 KASP (Kompetitive Allele-Specific PCR) markers, Jeonju624 was confirmed to be the near-isogenic line (NIL) of Saenuri with a 95.8% recovery rate. Jeonju624 is the NIL of Saenuri without LOX-3, and overcomes the linkage drag of Daw Dam with similar agronomic characteristics and genetic background to Saenuri. Jeonju624 can be utilized as a practical cultivar to improve the quality of stored rice, breeding material for the introgression of lox-3, and genetic material to elucidate the effect of introgressed genes. KCI Citation Count: 0